Chapter 37 Introduction to Section 6 Greenspace for healthy living - Barron, Sara (Routledge Environment and Sustainability Handbooks, 2022)
This handbook addresses a growing list of challenges faced by regions and cities in the Pacific;Rim, drawing connections around the what, why, and how questions that are fundamental;to sustainable development policies and planning practices. These include the connection;between cities and surrounding landscapes, across different boundaries and scales; the persistence;of environmental and development inequities; and the growing impacts of global;climate change, including how physical conditions and social implications are being anticipated;and addressed. Building upon localized knowledge and contextualized experiences,;this edited collection brings attention to place-;based;approaches across the Pacific Rim and;makes an important contribution to the scholarly and practical understanding of sustainable;urban development models that have mostly emerged out of the Western experiences. Nine;sections, each grounded in research, dialogue, and collaboration with practical examples and;analysis, focus on a theme or dimension that carries critical impacts on a holistic vision of city-;landscape;development, such as resilient communities, ecosystem services and biodiversity,;energy, water, health, and planning and engagement.;This international edited collection will appeal to academics and students engaged in;research involving landscape architecture, architecture, planning, public policy, law, urban;studies, geography, environmental science, and area studies. It also informs policy makers,;professionals, and advocates of actionable knowledge and adoptable ideas by connecting;those issues with the Sustainable Development Goals (SDGs);of the United Nations. The;collection of writings presented in this book speaks to multiyear collaboration of scholars;through the APRU Sustainable Cities and Landscapes (SCL);Program and its global network,;facilitated by SCL Annual Conferences and involving more than 100 contributors;from more than 30 institutions.